A dual-modal fluorometric and colorimetric nanoprobe based on graphitic carbon nitrite quantum dots and Fe (II)-bathophenanthroline complex for detection of nitrite in sausage and water. (15th May 2020) - Kong, Yuelin; Cheng, Qiao; He, Yu; Ge, Yili; Zhou, Jiangang; Song, Gongwu
Highlights: A dual-modal nanoprobe was established to detect nitrite. The detection mechanism was based on the inner filter effect and redox reaction. The method enabled the detection of nitrite in real samples. Abstract: A fluorometric and colorimetric dual-mode sensing platform based on graphitic carbon nitrite quantum dots (g-CNQDs) and Fe (II)-bathophenanthroline complex (BPS-Fe 2+ ) was designed to the sensitive detection of nitrite (NO2 − ) in sausage and water. In this system, the fluorescence of g-CNQDs was quenched by BPS-Fe 2+ complex due to the inner filter effect (IFE). When NO2 − was present, Fe 2+ was oxidized by nitrite to form BPS-Fe 3+ complex with BPS, leading to the recovery of the fluorescence from g-CNQDs. Therefore, we constructed a "turn-off-on" fluorescence probe for detection of NO2 − . Moreover, with the increase of NO2 − concentration, the color of the solution changed from red to colorless, so the UV–vis measurements and on-site visual detection were realized. The method is capable of detecting NO2 − in the concentration range of 2.32–34.8 μM with good selectivity and high sensitivity. In addition, the method has the potential to determine NO2 − in water samples and sausage samples.